Physiological and biochemical attributes of Mentha spicata when subjected to saline conditions and cation foliar application - Chrysargyris, Antonios; Solomou, Maria; Petropoulos, Spyridon A.; Tzortzakis, Nikos G. (My University, 2019)
Marginal water, including saline water, has been proposed as an alternative source of irrigation water for partially covering plant water requirements due to scarcity of adequate water supply in hot arid and semi-arid areas, such as those usually found in the Mediterranean basin. In the present study, spearmint plants (Mentha spicata L.) were grown in a deep flow hydroponic system under saline conditions, namely 0, 25, 50, and 100 mM NaCl. Moreover, foliar application of specific cations (K, Zn, Si) was tested as a means for alleviation of salinity stress under a plant physiological and biochemical approach. The results indicated that the highest salinity level of 100 mM NaCl severely affected plant growth, photosynthetic rates, leaf stomatal conductance, content of total phenolics and antioxidant status, while low to moderate salinity levels (25-50 mM NaCl) did not significantly affect plant growth and biochemical functions. In addition, leaf potassium and calcium accumulation decreased in saline-treated plants. Cations foliar application had small to no effect on plant growth, although it increased antioxidant activity and detoxified oxidative stress products/effects, through the increased enzymatic activities and proline accumulation. The present results have demonstrated that spearmint could be considered as a salinity tolerant species which is able to grow successfully under moderate salinity levels, while cation enrichment through foliar sprays was proved as a useful means to alleviate the stress effects caused by high salinity.
Keywords: Antioxidant activity; Cation foliar application; Hydroponics; Salinity; Spearmint